Answer :

(i)

= x3 - x2 + x + – (x2 - x3 + + x)


= x3 + x3 - x2 - x2 + x - x + -


= x3 - x2 - -


= x3 - x2 - -


(ii)


= a3 a2 – (a2 + a2 +


= a5 - a3 - a2 - a2 - - +


= (2a3 – 9a3) – (3a2 – 10a2) – +


= a3 - a2 - -


(iii)


= - - x2 – (x3 + x2 + x + )


= x3 - x2 - x2 - - + -


= x3 - x2- +


= x3 - x2 - – 1


(iv)


= - y2 – (y3 + y2 + y + )


= y3 - y2 - y2 - + -


= y3 + (-5y2 – 7y2) - y +


= y3 - y2 - y -


(v)


= ab - ac - bc – (ac - ab + )


= ab - ab - ac - ac - bc - bc


= - -


= ab - ac - bc


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Subtract:

NCERT - Mathematics Exemplar

Take away:
</p
RD Sharma - Mathematics

Subtract 3x-4y-7zRD Sharma - Mathematics

Subtract:

RD Sharma - Mathematics

If we subtract -3NCERT - Mathematics Exemplar

Add:

<spanNCERT - Mathematics Exemplar

State whether theNCERT - Mathematics Exemplar

Add:

<sNCERT - Mathematics Exemplar

Subtract:

NCERT - Mathematics Exemplar

Add:

<sNCERT - Mathematics Exemplar